Controlling photons in a box and exploring the quantum to classical boundary. Issue 10 (23rd September 2013) - Haroche, Serge; Blatt, Rainer; Bloch, Immanuel; Cirac, Ignacio; Zoller, Peter
<x xml:space="preserve">Abstract</x> Photons trapped in a superconducting cavity constitute an ideal system to realize some of the thought experiments imagined by the founding fathers of quantum physics. Physics laureate S. Haroche gives a personal account of the experiments performed with this "photon box" at the Ecole Normale Supérieure**. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>